2021
DOI: 10.1177/10556656211017409
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Outcomes After Cleft Palate Repair: Design and Implementation of a Perioperative Clinical Care Pathway

Abstract: Objective: To evaluate the development process and clinical impact of implementing a standardized perioperative clinical care pathway for cleft palate repair. Design: Medical records of patients undergoing primary cleft palate repair prior to pathway implementation were retrospectively reviewed as a historical control group (N = 40). The historical cohort was compared to a prospectively collected group of patients who were treated according to the pathway (N = 40). Patients: Healthy, nonsyndromic infants under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(56 citation statements)
references
References 13 publications
0
56
0
Order By: Relevance
“…Studies investigating the topic of pain and analgesia were the most common (n=31; Supplemental Table 5, Supplemental Digital Content 5, http://links.lww.com/SCS/E642)12,13. Many of the included studies investigated the use of various analgesia techniques that aimed at reducing postoperative opioid consumption 2,14–29. Seven of the included studies investigated the effectiveness of bupivacaine for use in nerve block in cleft lip and/or palate repair 1,4,28,30–33.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies investigating the topic of pain and analgesia were the most common (n=31; Supplemental Table 5, Supplemental Digital Content 5, http://links.lww.com/SCS/E642)12,13. Many of the included studies investigated the use of various analgesia techniques that aimed at reducing postoperative opioid consumption 2,14–29. Seven of the included studies investigated the effectiveness of bupivacaine for use in nerve block in cleft lip and/or palate repair 1,4,28,30–33.…”
Section: Resultsmentioning
confidence: 99%
“…Many of the included studies investigated the use of various analgesia techniques that aimed at reducing postoperative opioid consumption. 2,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Seven of the included studies investigated the effectiveness of bupivacaine for use in nerve block in cleft lip and/ or palate repair. 1,4,28,[30][31][32][33] All but 1 1 focused on infraorbital nerve block placement in cleft lip surgery patients.…”
Section: Pain and Analgesiamentioning
confidence: 99%
“…Due to the potential adverse effects of increased IV opioid use, reducing narcotic administration in infants is crucial. In addition, optimization of perioperative analgesia and opioid use has been associated with earlier feeding and, therefore, shorter lengths of hospital stay 3,9 . Prior studies have concluded that the use of intraoperative US-guided SMBs can potentially reduce postoperative pain and adverse outcomes during hospital stays.…”
Section: Discussionmentioning
confidence: 99%
“…Limiting postoperative pain is particularly important in pediatric cleft palate repair procedures. However, achieving adequate analgesic control through IV opioids can be challenging in young infants 9 . Due to the potential adverse effects of increased IV opioid use, reducing narcotic administration in infants is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…1). Following screening, 18 articles underwent full-text review and 5 studies [14][15][16][17][18] met final inclusion criteria. Upon initial review, 1 study was found to deliberately compare outcomes between controls and an ERAS group that was distinctly different with regards to demographics and medical history.…”
Section: Studies and Patientsmentioning
confidence: 99%